Instructional Media Provisions and Utilization for Teaching-Effectiveness in Classrooms - Soliu, Shittu Adeyemo; Elisha, Dauda (NIU Journal of Social Sciences; Vol 4 No 4 (2018): KIU Journal of Social Sciences, Vol. 4 No. 4, December 2018, 2019)
The paper examined instructional media provision and utilization for the effective teaching-learning process the concept, types and methods of provision were also examined. The instructional media were categorized into the audio, visual and audio â€“ visual aids. From the study, the available audio-visual aids were illustrated and categorized into projected and non-projected media. Both projected and non-projected media were also illustrated with relevant examples. The study identified the methods of making improvisation of the unavailable education media and their modes of utilization are also explored. It was therefore concluded that there is the need to make improvisation of the unavailable instructionalmedia for the effective teaching-learning processes. It was however recommended that the teachers should be motivated to make adequate improvisation of  instructional media in the interest of teaching. Learning process in Nigerian classrooms Keywords: Educational, media, teaching effectiveness and classroom.